Constraints on the CKM angle γ in B0→D̄0K*0 and B0→D0K*0 from a Dalitz analysis of D0 and D̄0 decays to KSπ+π- - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2009)
We present constraints on the angle γ of the unitarity triangle with a Dalitz analysis of neutral D decays to KSπ+π- from the processes B0→D̄0K*0 (B̄0→D0K̄*0) and B0→D0K*0 (B̄0→D̄0K̄*0) with K*0→K+π- (K̄*0→K-π+). Using a sample of 371×106 BB̄ pairs collected with the BABAR detector at PEP-II, we constrain the angle γ as a function of rS, the magnitude of the average ratio between b→u and b→c amplitudes. © 2009 The American Physical Society.